Synthesis and characterization of tin and nickel-tungsten thin films for transient liquid phase bonding - Cheng, Xin Wei (Nanyang Technological University, 2021)
In order to address the issue for the usage of electronic systems in harsh conditions such as high temperature applications, this project focuses on the reliability and resilience of the electronic packaging interconnect solder joints. A new soldering method called the Transient Liquid Phase (TLP) bonding that incorporates both dissolution bonding and diffusion bonding is developed. The process employs different low melting point materials, layered between the parent metals to produce joints with outstanding structural integrity where the bonds are able to withstand operations at temperatures above the bonding temperature once solidification is completed. This method has been made prominent for bonding in metallurgical systems. In this research study, nickel-tungsten thin films will be deposited using an effective electrolytic induced co-deposition method. Different electrolytes of varying compositions of nickel, tungsten and complexing agents were used, in conjunction with different current densities to determine the best electroplating condition for the co-deposition. Additionally, varying compositions of tungsten present in TLP bonding joints were tested using a die-shear test for studying the mechanical strength of the joint. An increase in bond strength was observed for void-free joints and an increase in the content of Ni and W present in the intermetallic phase formed after TLP bonding similarly increases the bond strength of the joint. From SEM and EDS analysis of the TLP bonding joints from Sn and Ni-W, intermetallic phases of different elemental compositions were formed. The intermetallic phase of Ni3Sn4 is formed at the interlayer region, previously occupied by the Sn foil used during TLP bonding. Other metastable ternary phases consisting of Ni, Sn and W were observed, namely T1, IMC1, IMC2 and IMC3 phases, likely to have an amorphous structure composed of nanocrystal grains.